Between Associational Autonomy and State Control: Nahdlatul Ulama and Muhammadiyah as Non-Party Political Intermediaries in Post-Reform Indonesia - Indawati; Rr. Indah Permatasari; Anisa Kurniatul Azizah; Alarico M. Tilmand Tilmand (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Nahdlatul Ulama (NU) and Muhammadiyah are influential nonpartisan Islamic organizations in Indonesia’s electoral politics, public policy, and state–society relations. This article examines the legal regulation of non-party political intermediation and the effects of preferential mining policies on religious organizational autonomy. Using a qualitative socio-legal approach, it combines doctrinal analysis of constitutional, civil society, mining, and judicial materials with a comparative study of NU and Muhammadiyah from 2017 to July 2026. The findings show that the 2017 amendment to the Law on Societal Organizations shifted safeguards from prior judicial review to ex post scrutiny of administrative dissolution. The law also insufficiently distinguishes policy advocacy, institutional political expression, elite conduct, electoral mobilization, and organizational resource use. NU relies more on personal authority and socio-religious networks, whereas Muhammadiyah emphasizes institutional structures, policy advocacy, and value-based politics. Mining privileges further create conflicts between watchdog functions and economic dependence on the state. The article proposes activity-based regulation grounded in attribution, transparency, proportionality, accountability, and conflict-of-interest control.